The equation of a circle can be written in the form (x-h)2 + (y - k)2 = r2, where r is the radius, and (h,k) is the center. So for your example, the equation would be: (x- 5)2 + (y - 3)2 = 72
x2+y2+4x+2y+3=0(x+2)2 + (Y+2.5)2 = 3This is the equation of circle with center at (-2,-2.5) with radius 3.5
9
Equation of the circle: (x-3)^2 +( y+13)^2 = 169
1. diameter 2. radius 3. center 4. edge
this is impossible
Centre of the circle: (3, 8) Radius of the circle: 2 Cartesian equation of the circle: (x-3)^2 + (y-8)^2 = 4
cxbdfbdb
Center of circle: (6, 8) Radius of circle: 3
center 5,-3 radius 4
If you mean a circle center at (3, 1) and a radius of 2 then the equation of the circle is (x-3)^2 +(y-1)^2 = 4
This makes no sence
The equation of a circle with center (2, -3) and radius 3 can be written as (x - 2)^2 + (y + 3)^2 = 3^2.
If you mean a circle center at (3, 1) and a radius of 2 then the equation of the circle is (x-3)^2 +(y-1)^2 = 4
(x-3)2+y2=144
I think it is center: (-4, 3) ; radius: 2 Apex:)
(x+3)2 + (y-5)2 = 9